Improving the Performance of Micro, Small and Medium Enterprises through Marketing Innovation and Financial Management in Pandansari Village, Ciawi District, Bogor Regency - Susy Hambani; Rohmat; Tini Kartini; Sudarijati; Muhammad Iksal Ilham; Yola Fitria Ramadanti; Agnes Wakei; Alma Nurul Febrianti; Dina Nurul Angelina Harahap; Fitra Weli; Mutiara Sibarani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The business relationships in this program are micro, small and medium enterprises Tiara's Kitchen and Yang Ibu. The problems faced by Tiara's Kitchen and Yang Ibu MSMEs are that there is still a lack of knowledge of MSME owners regarding the importance of marketing products through digital utilization and a lack of innovation in MSMEs to use product identities that can have an impact on customers, namely attractive product identities, besides that MSMEs do not conduct simple financial reports to determine sales prices and calculate the profits obtained. In accordance with these problems, this program conducts activities for product identity direction so that packaging, logos and banners in MSMEs are more attractive and digital marketing direction in the form of Shopee and Instagram applications is expected to increase sales, this program also conducts simple training for MSMEs to be able to carry out simple financial reporting activities.